Dynamic contrast-enhanced MRI in the differentiation of posttreatment fibrosis from recurrent carcinoma of the head and neck - OYSU, ÇAĞATAY (ELSEVIER SCIENCE INC, 2005)
Objective: The aim of this study was to investigate the value of dynamic contrast-enhanced magnetic resonance imaging (MRI) in the differentiation of posttreatment fibrosis from recurrent carcinoma, by comparing the dynamic contrast-enhancement characteristics of the lesions. Materials and methods: Twenty-six patients with previously treated carcinoma of the head and neck are studied by conventional and dynamic contrast-enhanced MRI at least 6 months after treatment by radiotherapy and/or surgery. Patients are divided into tumor-positive or -negative groups according to the radiological and clinical follow-up and biopsy. Lesion enhancement ratios at each dynamic sequence are calculated. Results: The tumor-positive group consisted of 11 patients, while the tumor-negative group included 15 patients. Between the two groups, lesion enhancement ratios are found to be significantly different (P<.05). Conclusion: Dynamic contrast-enhanced MRI may be a valuable modality in the differentiation of recurrent tumor from posttreatment fibrotic changes of the head and neck. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: magnetic resonance imaging; head and neck neoplasms; neoplasm recurrence, local; fibrosis; diagnosis, differential; NASOPHARYNGEAL CARCINOMA; BENIGN CONDITIONS; CANCER; TUMORS; ECHO; SUBTRACTION; RADIATION; IMAGES; CT